Panvascular concept in the evaluation and treatment of intracranial atherosclerotic stenosis - Tang, Jiahao; Zhou, Guoyang; Lu, Yuexin; Shi, Shunan; Cheng, Lin; Xiang, Jianping; Wan, Shu; Wang, Ming (Frontiers in Neurology, 2024)
Cerebrovascular disease is the leading causes of death and disability worldwide. Intracranial atherosclerotic stenosis (ICAS) is one of the major causes of ischemic stroke, especially in the Asian population. It is urgent to explore effective screening methods for early diagnosis to improve prognosis of patients with ICAS. Recently, the concept of panvascular medicine has provided a direction for the exploration of evaluation of ICAS. Based on the concept of “panvascular medicine,” atherosclerosis is the common pathological feature of panvascular disease, such as ICAS and coronary artery disease (CAD). In-depth research on the formation and development of plaques, the development and application of more precise preoperative assessment and detection methods, and the utilization of new interventional equipment have greatly enhanced the precision of diagnosis and treatment of CAD. Studies attempt to apply similar evaluation and treatment in ICAS. The deeper understanding, the more accurate diagnosis and treatment, contributing to improve the prognosis of patients with ICAS. This review focuses on these evaluations and treatment of CAD applied in the field of ICAS.